Tinjauan Yuridis Tindak Pidana Pencurian Dengan Pemberatan Yang Dilakukan Secara Berlanjut Putusan Nomor 1271/Pid.B/2023/PN Lbp - Lusiani Silalahi; Tri Reni Novita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Cases of criminal acts of theft with ongoing aggravations, as regulated in various court decisions, criminal law provisions often give the impression that there is only one main perpetrator who is charged with criminal sanctions for each criminal act. Shows how criminal law must respond to situations where crimes are committed repeatedly and involve more than one individual. In general, participation can be interpreted as an act (criminal act) carried out by more than one person. Therefore, determining the position of the perpetrator in a criminal act is very important. Perpetrators in the general sense of plea must be distinguished from perpetrators in the formulation of Article 55 paragraph (1).The aim of this research is to determine the Juridical Review of the Crime of Theft with Continuous Aggravation. The location for data collection in this research was at the Galang Police Criminal Investigation Unit, Deli Serdang Police on Jl. Perintis Independen No 1 Galang Kota, Galang sub-district, Deli Serdang Regency. The type of research used in this research is empirical research, namely legal research carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Researchers can use one or a combination of techniques depending on the problem being faced or being researched. The data analysis technique used in this legal research uses qualitative analysis.Based on the research results, in Decision Number 1271/Pid.B/2023/PN Lbp regarding the crime of theft with ongoing aggravation, various causal factors and legal considerations show the complexity of the case. The main causal factors include economic and social conditions that encourage individuals to look for shortcuts in meeting their living needs, as well as the influence of the social and social environment which can increase the risk of involvement in criminal acts. Lack of access to education and training, as well as psychological factors such as emotional disorders and certain personality characteristics, also play a significant role in driving criminal activity.It can be concluded that the application of Article 363 Paragraph (1) 3rd and 4th of the Criminal Code, the Panel of Judges considered that the defendant's actions fulfilled the elements of the crime of theft with aggravation as regulated in Article 363 Paragraph (1) 3rd and 4th of the Criminal Code.